Tensile analysis of loop joints with different overlap lengths - Kai Wang; Gang Liu; Congquan Wang; Fenglin Wang (Journal of Asian Architecture and Building Engineering)
In order to achieve rapid bridge construction, on-site wet joint joining techniques for prefabricated bridge decks are commonly used. The primary method involves mainly lap welding, but this form poses some drawbacks such as difficult lap jointing of two steel bars and a hefty welding workload. To address these issues, this study conducts model experiments on the unwelded structure of loop joints. We compare and analyze the displacement, crack distribution, crack development process, and strain variability of loop joints across three different overlap lengths, along with one type of straight bar lap-welded wet joints. It is observed that, despite the comparable ultimate tensile capacity of loop joints with the main rib to that of the welded wet joint with the main rib, the failure mode varies, and the crack direction changes with the overlap length. From a structural stress perspective, if the U-bar of the loop joint meets a specific overlap length, the wet joint adequately fulfills stress requirements and can be applied in practical engineering.